2021
DOI: 10.26886/2414-634x.2(46)2021.3
|View full text |Cite
|
Sign up to set email alerts
|

Choice of Anesthesia Method for Transforaminal Endoscopic Discectomy (Tfed)

Abstract: Transforaminal endoscopic discectomy (TPED) is a modern effective method of removing symptomatic hernias in the lumbar spine that cause therapeutically resistant pain syndromes. It gained its popularity due to its safety and minimally invasiveness. To avoid injury to the nervous system, this operation must be performed with the patient's clear consciousness. Combined anesthesia (CA), which combines a local anesthetic with an opioid analgesic and epidural anesthesia (EA), are alternative methods of anesthesia, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…This was corroborated by another study, which reported a 28% incidence of nausea and vomiting when local anesthesia was supplemented with opioids during endoscopic discectomy. [ 4 ]…”
Section: Discussionmentioning
confidence: 99%
“…This was corroborated by another study, which reported a 28% incidence of nausea and vomiting when local anesthesia was supplemented with opioids during endoscopic discectomy. [ 4 ]…”
Section: Discussionmentioning
confidence: 99%